Niveles de aplicación de las normas de bioseguridad en granjas avícolas del cantón cumandá, ecuador - Ávila Preciado, Sergio Moisés (2024)
The present study evaluated compliance with biosecurity standards in poultry farms in the canton of Cumandá, Ecuador, as well as to determine the degree of knowledge of workers about these measures, to identify the impact of biosecurity on them. Evaluations were carried out through surveys to owners and administrators in 15 poultry farms, covering criteria and indicators: infrastructure, hygienic measures, animal welfare and health, it was of a non experimental nature of transitional type, its weighting was distributed from 90 to 100 points for poultry farms with excellent biosecurity; standard and does not meet; its rating between 0, 1 and 2 for implementation or operation, deficiency and not implemented respectively according to Agroquality regulations; The results revealed that some farms implement biosecurity measures, others do not fully comply with established regulations, it was observed in infrastructure criteria, with 25.50 points for large farms was more representative with respect to small and medium farms, since producers invest in management technology and quality; it was found with 15.80 points; In terms of hygienic, safety and security measures, 7.80 were observed for small farms; in animal welfare, 14.30 points was the best answer; In animal health criterion 14.50 for large farms, with an overall weighting of 70.10 /100 points for them, with respect to small and medium-sized farms that do not adequately comply with hygiene and safety measures. It is suggested to implement training programs for workers, establish regular monitoring and evaluation systems, improving biosecurity practices in poultry production in the Cumandá canton.